Hubungan Bimbingan Belajar dalam Keluarga dengan Prestasi Belajar Matematika Kelas Tinggi SDN 26 Watang Palakka - RESMA OCTAVIANTY; Sidrah Afriani Rachman; Ruka yah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The problem in this study is the lack of tutoring in the family has an urgent task in education. This study is a quantitative study with a correlation model that aims to determine the relationship betweem tutoring in the family and high grade  mathematics learning achievement at SDN 26 Watang Palakka, The data analysis technique using statistical analysis obtained tutoring in the family has an average of 84,5 and a percentage of 84,5% and the average student learning achievement in mathematics is 82,17 and an achievement of 82,17% with a very good category. Then based on the results of inferential statistical analysis, it shows that  (5,5406) is greater (>) than the value of  (1,66277) at a significant level of 5% so that it can be concluded that there is a significant relationship between tutoring in the family and learning achievement in mathematics students from these conclusions. The impact generated in this study with the existence of tutoring in the famiy can improve student achievement.